2012
DOI: 10.3892/ijo.2012.1614
|View full text |Cite
|
Sign up to set email alerts
|

miR-203 inhibits the migration and invasion of esophageal squamous cell carcinoma by regulating LASP1

Abstract: The expression of microRNA-203 (miR-203) in esophageal squamous cell carcinoma (ESCC) tissues is remarkably lower than that in non‑ESCC tissues. We investigated how miR-203 could influence the development of ESCC cells. Our analyses revealed that miR-203 inhibited the migration and invasion of ESCC cells. Genome-wide gene expression data and target site inhibition assays showed that miR-203 appears to directly regulate LIM and SH3 protein 1 (LASP1). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 39 publications
2
43
0
Order By: Relevance
“…In the recent study, miR-203 has significantly low expression in cancer tissues compared to non-tumor counterparts (Viticchiè et al, 2011;Takeshita et al, 2012;Gu et al, 2013), while there were up-regulation of miR-203 was observed in pancreatic adenocarcinomas and breast, cancers (Naoki et al, 2010;Madhavan et al, 2012), we think the differential expression of miRNAs may be the result of tissue-specific differences. Just as Baffa et al suggested (Baffa et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent study, miR-203 has significantly low expression in cancer tissues compared to non-tumor counterparts (Viticchiè et al, 2011;Takeshita et al, 2012;Gu et al, 2013), while there were up-regulation of miR-203 was observed in pancreatic adenocarcinomas and breast, cancers (Naoki et al, 2010;Madhavan et al, 2012), we think the differential expression of miRNAs may be the result of tissue-specific differences. Just as Baffa et al suggested (Baffa et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Just as Baffa et al suggested (Baffa et al, 2009). miR-203 was proved to be down-regulated in squamous cell carcinoma (Yuan et al, 2011;Boldrup et al, 2012;Takeshita et al, 2012). Expression profiling using quantitative real-time RT-PCR of 202 miRNAs was performed on micro-dissected highgrade CIN (CIN 2/3) tissues and compared to normal cervical epithelium, then Cheung TH found miR-203 could distinguished the high-grade CIN specimens from normal cervical epithelium (Cheung et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It can also target Hakai and inhibit the growth of human colon adenocarcinoma (28). Additionally, those genes involved in the regulation of cell proliferation, apoptosis, cell cycle progression, migration and invasion, are also the targets of miR-203, including Robo1, Kif5b, E2F3, LASP1, ASAP1, PKCα, BIRC5, Bmi-1 and DeltaNp63 (23)(24)(25)(26)(29)(30)(31)(32)(33). Whether these miR-203 targets are also involved in the development and progression of NB remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the clinical challenge that a significant proportion of these patients are erroneously misdiagnosed using these conventional pathological criteria, incorporating more robust molecular biomarkers, such as the quantification of miR-203 expression in serum, followed by the preoperative selection of patients without lymph node metastasis, could promote minimally invasive treatment of early GC. MiR-203 is reported to function as a tumor-suppressive miRNA in many types of cancer studied in tissues and cell lines [28][29][30][31][32][33]. Ectopic expression of miR-203 in prostate cancer cell lines could influence proliferation, apoptosis, and migration [32], and overexpression of miR-203 in laryngeal carcinoma cells reduces cell viability and leads to cell-cycle arrest in G1 phase [31].…”
Section: Discussionmentioning
confidence: 99%